PENGEMBANGAN LKS HOTS BERBASIS WEBSITE PADA TEMA MAKANAN SEHAT UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA MI - Ifa Zuhria; Wahidmurni; Indah Aminatuz Zuhriyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
ts’ critical thinking is very necessary because they are faced with high global conditions, especially competition in the educational context. Hence, the development of advanced technology and the demands of technology utilization in the educational context are one of the main needs. In addition, thematic learning is one of the benchmarks subject for successful learning at the MI/SD levels, because thematic is a subject that put several learning subjects into one learning subject so the development of thematic learning needs new innovations. The study in this article is designed to (1) describe the specific design of the LKS HOTS as a suitable, effective, interesting, and practical learning media to improve critical thinking for MINU students at Wonosari District in Malang, and (2) analyze the feasibility and attractiveness of Website-based LKS Hots development on the healthy food theme to improve MI students’ critical thinking, (3) describe LKS HOTS to improve MI students' critical thinking. The method used in this study is Research and Development (RnD) which used quantitative research referring to the theory of Borg & Gall which has been reduced into 7 stages. The sample in this study involved the students of class V MINU Plandi 02 Malang. Data collection instruments used were observations, interviews, questionnaires, and tests. The validation of LKS HOTS was validated by three experts, material experts, presentation experts, and linguists and try-out in class V MINU Wonosari Malang. The results of this developmental study involved (1) the results of the Website-based LKS HOTS product which could be applied as a learning source for the students. (2) This product was proven to be interesting and feasible to use. Based on the validation results, it was obtained that validation from design experts with a percentage of 93.33%, material expert validation by 96.9%, and validation from linguists at 95.83%. Whilst try-out results showed a practicality percentage of 96.24%, the percentage of the attractiveness of 98.39%, individual trials of 93%, group trials of 94.19%, and limited trials of 98.92%. (3) This product was successful to improve the student’s critical thinking by applying Pretest and Posttest assessments which have been processed by using the Paired Simple t-test formula and obtained a significance value of 0.000, thus Ho was rejected. It means that there was a significant difference between before and after using website-based LKS HOTS development on healthy food themes to improve MI students’ critical thinking.